Corruption in business: hard to detect and even harder to quantify - Kása, Richárd; Réthi, Gábor; Németh, Tamás; Szászvári, Karina (Vezetéstudomány / Budapest Management Review, 2024)
Researching corruption is difficult because subjects’ preconceptions can distort the empirical process. There is, however, a growing interest in the subject: the perception of economic performance, the investment environment and other areas of the economy depends on a country’s level of corruption, which a variety of indicators and methods can characterise. Individual attitudes and perceptions of the phenomenon in a given country can, however, help us better understand it and provide a more realistic picture. The authors examined the attitudes of individuals towards the perception, not the experience, of corruption, including how he or she relates to corrupt situations, judges the participants’ behaviour and how he or she would likely behave in a similar situation. Their vignette rating system surveyed 261 entrepreneurs. Entrepreneurs’ sensitivity and likelihood of corrupt behaviour were measured to reveal entrepreneurs’ views on business and government corruption.